Sistem Pengendalian Manajemen Produksi Dan Hubungannya Dengan Pengelolaan Persediaan Bahan Baku (Studi Kasus pada PT. Indra Brotherâs di Bandar Lampung) - Thontowie Dauli; . Septenaria; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of this study was to determine how the management control system that is run by PT. Pola Marmer Kencana against baku. Material inventory method management analysis is qualitative analysis by using the theories in connection with the problems and issues and at the same time compare realities in the company. The analysis finds that the production process there are weaknesses in the company, this is because the control of management that are less well so no control over the production engine that would impede the course of the production process. From the results, it can be concluded that the production management control system for the management of inadequate supply of raw materials, in the absence of management control, especially on a production machine, so that it would impede the course of the production process. Therefore, companies should create a separate section in the organizational structure so that there is a part that controls the system and fix the machine if one day the damage occurred.